The game of negotiations: Ordering issues and implementing agreements - Lutz-Alexander Busch; Ignatius J. Horstmann (The University of Western Ontario, Department of Economics, 2000)
We use a two-issue bargaining model with asymmetric information to study agent choice of how to structure bargaining. We uncover the settings in which different agenda structures are chosen in equilibrium, how the order in which issues are bargained over matters, and what impact the rules for implementing agreements have. If agreements are implemented as they are reached, 'easy' issues are negotiated first and 'hard' issues later; if agreements are implemented only after all issues are settled, then it is size that matters, with large issues settled first. All parties prefer the former rules of implementation to the latter.
Keywords: C7; 330; Verhandlungstheorie; Asymmetrische Information; Signalling; Theorie; Ranking-Verfahren